Faktor yang Memengaruhi Niat Wisatawan Jabodetabek Kembali Ke Pulau Bali Semasa Covid-19 - Audina, Fahmi Idris; Natalia, Theodosia C.; Lemy, Diena Mutiara; Hulu, Meitolo (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
The purpose of this research is to analyze the effect of motivation, travel constraints, and destination image on Greater Jakarta tourists’ revisit intentions to Bali during the Covid-19 pandemic. This study emphasizes four variables consists of tourist motivation (X1), travel constraints (X2), destination image (Z), and revisit intention (Y). Purposive sampling collects 297 respondents who lived in Greater Jakarta and visited Bali during the Covid-19 pandemic. This study uses the PLS-SEM analysis technique to identify the influence between variables. The results showed that tourist motivation had a positive and significant effect on the destination image and the revisit intention. Contraryly, travel constraints had a negative and significant effect on destination image and revisit intention. With this research, tourism businesses can use the findings of this study as a reference when developing Bali tourism marketing strategies